2015
DOI: 10.1021/acs.inorgchem.5b01022
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) Monomer and Dimer Complexes with a Bis(oxazolinyl)phenyl Pincer Ligand

Abstract: A series of platinum(II) complexes with the formulas Pt(phebox)(L)(+) (phebox(-) = 1,3-bis(4,4'-dimethyl-2'-oxazolinyl)phenyl anion; L = pyridine (py), 4-phenylpyridine, quinoline, acridine) and Pt2(phebox)2(μ-L')(2+) (L' = pyrazine, 4,4'-bipyridine, 1,2-bis(4-pyridyl)ethane) was prepared. Crystallographic data establish that the metal center is bonded to the tridentate phebox(-) and monodentate pyridyl ligands. The five-membered oxazoline rings favor a CH2-CMe2 twist conformation. Pt(phebox)Cl and Pt(phebox)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…The luminescence properties of the cyclometalated platinum(II) complexes make them appropriate candidates for investigation by many research groups . Regarding these properties, cycloplatinated(II) complexes have various applications such as in light‐emitting devices, dye‐sensitized solar cells, photoswitches, photocatalysts and chemical or biochemical sensors .…”
Section: Introductionmentioning
confidence: 99%
“…The luminescence properties of the cyclometalated platinum(II) complexes make them appropriate candidates for investigation by many research groups . Regarding these properties, cycloplatinated(II) complexes have various applications such as in light‐emitting devices, dye‐sensitized solar cells, photoswitches, photocatalysts and chemical or biochemical sensors .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the luminescence properties of cycloplatinated (II) complexes have always been important subjects in many outstanding research groups . Room temperature phosphorescence in these complexes requires a chromophoric cyclometalated ligand and a Pt atom which is able to allow singlet–triplet intersystem crossing due to its high spin–orbit coupling constant.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no such reports, because most conventional vaulted complexes have been designed to be as rigid as possible for synthetic and functional reasons, which has probably led to this chemistry being unascertained up to now. As a part of a program aimed at the development of new functional materials based on controlled d–π conjugation platforms bearing three‐dimensional overall structures,, , we have found that novel polymethylene‐vaulted Pt complexes bearing ( N ^ C ^ N ) tridentate cyclometallating ligands ( 1 and 2 ) undergo remote hydrogen bonding to form intramolecular M–H interactions between Pt atom and linker hydrogens, where the regiospecificity of the interactions in long alkyl chains is altered upon variation of the linker length (Scheme ). In this paper, we report the synthesis, structure and conformational study of complex 1 and 2 with a focus on the structure‐dependence of the Pt–H interactions as a key factor for conformational fixation of the vaulted complexes.…”
Section: Introductionmentioning
confidence: 99%
“…ArH24,26 ), 7.09 (t, J = 7.5 Hz, 1 H, ArH 4 ), 7.36(d, J = 8.6 Hz, 2 H, ArH23,27 ), 7.49(d, J = 7.5 Hz, 2 H, ArH 3,5 ),8.41 [(66 %) s, (34 %) d, 3 J PtH = 131.3 Hz, 2 H, N=CH7,8 ] ppm 13. C NMR (125 MHz, CDCl 3 ): δ = 21.…”
mentioning
confidence: 99%